2017
DOI: 10.2217/nnm-2017-0124
|View full text |Cite
|
Sign up to set email alerts
|

Sageretia Thea (Osbeck.) Mediated Synthesis of Zinc Oxide Nanoparticles and Its Biological Applications

Abstract: Hemocompatible nature of bioinspired nanoparticles was revealed. Furthermore, the antioxidant activities were performed. In addition, significant protein kinase while insignificant alpha amylase inhibition were recorded.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
65
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 156 publications
(78 citation statements)
references
References 68 publications
11
65
2
Order By: Relevance
“…(Figure 7a). Linear relationship between PZO NFs concentration and antifungal activity enhancement can be attributed to the consequent incremental ROS production as reported earlier [60][61][62]. Toxicological pattern of PZO NFs against targeted strains may vary depending upon various factors in addition to the morphological and size ranges of PZO NFs.…”
Section: Antimicrobial Efficacy 34supporting
confidence: 64%
“…(Figure 7a). Linear relationship between PZO NFs concentration and antifungal activity enhancement can be attributed to the consequent incremental ROS production as reported earlier [60][61][62]. Toxicological pattern of PZO NFs against targeted strains may vary depending upon various factors in addition to the morphological and size ranges of PZO NFs.…”
Section: Antimicrobial Efficacy 34supporting
confidence: 64%
“…Traditional medicines (antibiotics) are often used for bacterial infections but certain problems are associated with them such as antibiotic resistance. Scientific community is engaged to develop new approaches to resolve the issue of antibiotic resistance and minimize the risk of its development . In current study, NiONPs has shown strong antibacterial and antifungal potentials.…”
Section: Discussionmentioning
confidence: 99%
“…However, the ITO lms are brittle and easily broken by an externally applied bending force, which have high brittleness and poor exibility. 1,2 With the development of technology and society, in order to meet people's needs for medicine, 3 exible touch screens, 4 solar cells, 5 wearable devices, 6 etc., AgNWs are attracting much attention for their unique electronic conductivity and good exibility. Therefore, it is very necessary to study and prepare high-quality AgNWs, making it become an ITO replacement material with realistic application prospects, especially as a popular material for exible screen production.…”
Section: Introductionmentioning
confidence: 99%